The Effect of Seawater Used for Hydrodistillation on Essential Oil Yield and Composition of Oil-Bearing Rose (Rosa damascena Mill.) - Nimet Kara; Sabri Erbaş; Hasan Baydar (International Journal of Secondary Metabolite)
Oil-bearing rose (Rosa damascena Mill.) is the most important rose species having a high-value volatile oil, used in the fragrance and cosmetic industries. Epidermal cells of the flower petals are the main essential oil source. During the boiling process of hydrodistillation, the essential oil in the cells diffuses through the cell walls by means of osmosis. The purpose of this research was to find out what happens when seawater or salt water used instead of distilled water for hydrodistillation. Fresh rose flowers collected at full blooming stage in the early hours of morning were distilled with pure water (control) and Mediterranean seawater using Clevenger hydrodistillation apparatus. Constituents of essential oils obtained by hydro distillation were identified with GC-FID/MS apparatus. Essential oil yield were not significantly affected by the distillation practices. However, the hydrodistillation with seawater gave a little higher yield as 0.045% than the hydrodistillation with pure water as 0.042%. A total of 23 essential oil constituents were detected by GC-FID/MS analyses. The main compounds in both rose oils distilled by tap water and seawater were citronellol, geraniol, nerol, and nonadecane. As results, hydrodistillation of oil-bearing rose with seawater provided a statistically insignificant increase in the essential oil yiled from 0.040 to 0.045%, but caused a significant decrease in citronellol rate from 41.49 to 33.56 %, and significant inceraeses in geraniol rate from 17.58 to 27.44 % and nerol rate from 6.45 to 12.21 %. The results obtained from this research should be examined in more detail at industrial scales.